Improving drying efficiency and energy saving for crumb natural rubber drying with combined drying technologies - Tham, Thing Chai (2018)
Natural rubber (NR) or cis-1, 4-polyisoprene is obtained from the latex that is tapped from a tree known as Hevea Brasiliensis. It can be in the form of preserved latex concentrates or further processed into sheets, crepes, block rubber that associated with its unique characteristics such as great elongation strength, excellent building tack, low rolling resistance, low heat build-up and good low-temperature performance. These are essential characteristics in dynamic working environment and application especially for vehicle tyre and rubber thread. To produce good quality of technically specified rubber or block rubber from raw natural rubber, drying process plays a vital role in the raw rubber processing. To date, the level of technology involves rubber drying is still inefficient and primitive. Non-uniform drying and the occurrence of wet rubber in the final product are the major drawbacks when using the conventional type of trolley dryer. Also, fuel and electricity usage for a single drying operation is noticeably intense and costly. Indeed, the main limitation of conventional drying method is the drying time that is mainly dependent on temperature gradient inside the product and cannot be sustainably reduced because the product is heat sensitive; whereas drying at high temperature for prolong hours could result in quality deterioration too.